Sotatercept Use in a Patient with Pulmonary Arterial Hypertension Undergoing Lung Transplantation - Justin P. Rosenheck; Kashika Goyal; Tara Fallah; Pamela Burcham; Kukbin Choi; Matthew Henn; Elie Homsy; Scott Visovatti; Veronica Franco (JHLT Open)
Pulmonary arterial hypertension (PAH) is one of the common indications for lung transplantation. Sotatercept is a new medication with a novel mechanism of action and was recently approved for the treatment of PAH. Sotatercept is associated with significant adverse effects including thrombocytopenia and erythrocytosis which can impact outcomes of lung transplantation. This is the first described case of a patient undergoing lung transplantation while receiving sotatercept for PAH.